2018
DOI: 10.1177/0956247818804343
|View full text |Cite
|
Sign up to set email alerts
|

Providing basic services under siege: preliminary insights from interim councils and medical providers in besieged urban areas of Syria

Abstract: The interim councils and medical workers operating in besieged cities in opposition-held areas of Syria have faced enormous challenges in providing services to citizens. Despite the extremely difficult operating environment, some semblance of organized government has been installed by anti-regime rebels, whose functions include provision of basic services. Data collected from interviews with interim councils and medical workers in four opposition-held areas suggest that despite the acutely constrained environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“… Damascus None Khamis (2018) [ 54 ] First: Syria Last: Lebanon First: government Last: academic Reports National AIDS Program data and examines how the war affected HIV surveillance and voluntary counselling and testing Health status; health system (service provision) 2010–2016 Secondary analysis of National AIDS Program surveillance data General population National Not reported Kubitary (2018) [ 55 ] First: Syria Last: Syria, France First: academic Last: academic Examines validity of the Arabic version of the two-question Quick Inventory of Depression (QID-2-Ar) in Syrian multiple sclerosis patients. Health status Not reported Cross-sectional study Multiple sclerosis patients aged 18–60 years seen at two hospitals Damascus None Kubitary (2018) [ 56 ] First: Syria Last: France, Syria First: academic Last: academic Examines the effects of Therapy by Repeating Phrases of Positive Thoughts (TRPPT) on PTSD, Sleep Disorder and War Experiences among school children and adolescents Health systems (service provision); health status Not reported Clinical trial Children & adolescents aged 13–17 years Damascus Not reported Meiqari (2018) [ 57 ] First: Netherlands Last: Netherlands First: humanitarian, academic Last: humanitarian Describes the impact of the war on child health in Tal Al-Abyad and Kobane, using available medical and humanitarian data from Médecins Sans Frontières Health status; humanitarian assessment, response or needs April 2013–September 2016 Analysis of MSF clinical data and reports Children < 5 years old who attended an MSF facility Aleppo, Al-Raqqa Not reported Morrison (2018) [ 58 ] First: UK Last: N/A First: academic Reports the experiences and challenges of health service delivery under siege Health system (service provision); war strategies / alleged IHL violations Mid-2016 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Damascus None Khamis (2018) [ 54 ] First: Syria Last: Lebanon First: government Last: academic Reports National AIDS Program data and examines how the war affected HIV surveillance and voluntary counselling and testing Health status; health system (service provision) 2010–2016 Secondary analysis of National AIDS Program surveillance data General population National Not reported Kubitary (2018) [ 55 ] First: Syria Last: Syria, France First: academic Last: academic Examines validity of the Arabic version of the two-question Quick Inventory of Depression (QID-2-Ar) in Syrian multiple sclerosis patients. Health status Not reported Cross-sectional study Multiple sclerosis patients aged 18–60 years seen at two hospitals Damascus None Kubitary (2018) [ 56 ] First: Syria Last: France, Syria First: academic Last: academic Examines the effects of Therapy by Repeating Phrases of Positive Thoughts (TRPPT) on PTSD, Sleep Disorder and War Experiences among school children and adolescents Health systems (service provision); health status Not reported Clinical trial Children & adolescents aged 13–17 years Damascus Not reported Meiqari (2018) [ 57 ] First: Netherlands Last: Netherlands First: humanitarian, academic Last: humanitarian Describes the impact of the war on child health in Tal Al-Abyad and Kobane, using available medical and humanitarian data from Médecins Sans Frontières Health status; humanitarian assessment, response or needs April 2013–September 2016 Analysis of MSF clinical data and reports Children < 5 years old who attended an MSF facility Aleppo, Al-Raqqa Not reported Morrison (2018) [ 58 ] First: UK Last: N/A First: academic Reports the experiences and challenges of health service delivery under siege Health system (service provision); war strategies / alleged IHL violations Mid-2016 …”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one papers cover issues of service provision including renal [ 17 ], mental health [ 20 , 24 , 56 ], orthopaedic [ 73 ], cancer [ 40 ], communicable disease surveillance [ 54 ], respiratory [ 87 ], antenatal [ 93 ], and trauma services [ 25 , 74 , 89 ], disruptions to service provision due to attacks on healthcare [ 35 , 36 , 49 , 52 , 67 ], challenges of service provision under siege [ 58 , 80 ], factors enabling sustained UNRWA service delivery [ 85 ], and interplays of local service provision with cross-border humanitarian assistance [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations